Techno Economic of CNG & GTG Technology Applied in Gas Flare Management - Nafiscatoha, Dicgorry; Saksono, Nelson (Universitas Muhammadiyah Surakarta, 2019)
Our environment is being endangered by greenhouse gases from gas flaring processes. Approximately 4 mmscfd is contributed by flare gas from JWB field. The flare gas would be concentrated to become the most economic value and prevent the greenhouse effect. The analysis of economic value is getting the fastest investment return and the most annual profit. This Study would discuss a techno-economic aspect of flare gas utilization technology. In this paper, two methods of compressed natural gas (CNG) and gas to wire (GTW) was combined with CNG would be introduced and applied in this field. For both methods are introduced and compared to the best method from an economic standpoint identified. According to the results, the production of the CNG method of flare gas utilization is the most economical technology; with has a greater ROR, an annual profit of about 3.65 million, and a payback period of 2.09 years. Economic analysis shows there improved gas flare value and improvement environmental protection.